Effect of Kinetin on Growth and Biomass Production in Alangium lamarckii Thwaites - Ahirwar, J. R. (Indian Forester, 2013)
An attempt has been made to evaluate the influence of kinetin on seedling growth and biomass production of Alangium lamarckii. The result reveals that the formation of lateral branches and higher growth performance of Alangium lamarckii can be achieved by spraying 100ppm of kinetin on one month old seedlings. The growth and dry weight accumulation of seedling increased with the increase in concentration of kinetin as compared to control.